2018
DOI: 10.1183/13993003.01770-2018
|View full text |Cite
|
Sign up to set email alerts
|

Introducing molecular testing of pyrazinamide susceptibility improves multidrug-resistant tuberculosis treatment outcomes: a prospective cohort study

Abstract: ERSpublications Early availability of reliable PZA drug-susceptible testing is a prerequisite for successful MDR-TB treatment. The optimised regimen achieved a treatment success rate of 82.4% and shortened the course to 12 months for PZA-susceptible patients http://ow.ly/ObdI30n3GF7

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 47 publications
5
19
0
Order By: Relevance
“…[22][23][24][25][26] It has been reported that patients with early available molecular DST results had a more rapid culture conversion and higher rate of treatment success. 27,28 The RDBH assay we built took only 7 h from multiplex PCRs to provide results and allowed the simultaneous analysis of 42 clinical DNA samples for FQs and SLID susceptibility, which was comparable to that needed by the MTBDRsl v2.0 based on isolates and were obviously less than the time (6 weeks) needed for L-J slants based DST. 29 The present study also provides detailed performance of the RDBH assay on predicting KN, AMK and CPM resistance and XDR by comparing to the phenotypic DST and sequencing.…”
Section: Discussionmentioning
confidence: 99%
“…[22][23][24][25][26] It has been reported that patients with early available molecular DST results had a more rapid culture conversion and higher rate of treatment success. 27,28 The RDBH assay we built took only 7 h from multiplex PCRs to provide results and allowed the simultaneous analysis of 42 clinical DNA samples for FQs and SLID susceptibility, which was comparable to that needed by the MTBDRsl v2.0 based on isolates and were obviously less than the time (6 weeks) needed for L-J slants based DST. 29 The present study also provides detailed performance of the RDBH assay on predicting KN, AMK and CPM resistance and XDR by comparing to the phenotypic DST and sequencing.…”
Section: Discussionmentioning
confidence: 99%
“…This cohort study was performed at two hospitals located in Zhejiang Province, China, and initiated by the Zhejiang Disease Control and Prevention Center (CDC) which has set up routine drug resistance monitoring for TB since 1999 10. The two clinical studies were completed in both the hospitals: one singer-arm study was supported by the Global Fund MDR-TB Project,11 and another cohort study entitled “Optimization of MDR-TB Treatment Regimen Based on the Molecular Drug Susceptibility Results of Pyrazinamide” was registered on ClinicalTrial.gov with number NCT02120638 12. To acquire complete follow-up information, we screened the patients in the two studies regarding eligibility consecutively.…”
Section: Methodsmentioning
confidence: 99%
“…In a recent study, SUN et al [21] present interesting data from China in a prospective cohort of MDR-TB cases where pyrazinamide resistance was or was not tested. The study results show that optimisation of treatment regimens based on pyrazinamide DST significantly improves treatment outcomes [21].…”
Section: Dots-plusmentioning
confidence: 99%
“…The potential wide use of the regimen will, as for BPaL, be conditional to minimisation of creation of resistance to its new components. Concerningly, the presence of resistance to the fluoroquinolones and pyrazinamide among rifampicin-resistant cases, although frequently low, is already well documented in certain settings [20,21,37].…”
Section: While This Historical Account Summarises the Past And Presenmentioning
confidence: 99%